Review of Research on Supercritical Carbon Dioxide Axial Flow Compressors - Yong Tian; Dexi Chen; Yuming Zhu; Peng Jiang; Bo Wang; Xiang Xu; Xiaodi Tang (Energies)
Since the beginning of the 21st century, the supercritical carbon dioxide (sCO2) Brayton cycle has emerged as a hot topic of research in the energy field. Among its key components, the sCO2 compressor has received significant attention. In particular, axial-flow sCO2 compressors are increasingly being investigated as power systems advance toward high power scaling. This paper reviews global research progress in this field. As for performance characteristics, currently, sCO2 axial-flow compressors are mostly designed with large mass flow rates (>100 kg/s), near-critical inlet conditions, multistage configurations with relatively low stage pressure ratios (1.1–1.2), and high isentropic efficiencies (87–93%). As for internal flow characteristics, although similarity laws remain applicable to sCO2 turbomachinery, the flow dynamics are strongly influenced by abrupt variations in thermophysical properties (e.g., viscosities, sound speeds, and isentropic exponents). High Reynolds numbers reduce frictional losses and enhance flow stability against separation but increase sensitivity to wall roughness. The locally reduced sound speed may induce shock waves and choke, while drastic variation in the isentropic exponent makes the multistage matching difficult and disperses normalized performance curves. Additionally, the quantitative impact of a near-critical phase change remains insufficiently understood. As for the experimental investigation, so far, it has been publicly shown that only the University of Notre Dame has conducted an axial-flow compressor experimental test, for the first stage of a 10 MW sCO2 multistage axial-flow compressor. Although the measured efficiency is higher than that of all known sCO2 centrifugal compressors, the inlet conditions evidently deviate from the critical point, limiting the applicability of the results to sCO2 power cycles. As for design and optimization, conventional design methodologies for axial-flow compressors require adaptations to incorporate real-gas property correction models, re-evaluations of maximum diffusion (e.g., the DF parameter) for sCO2 applications, and the intensification of structural constraints due to the high pressure and density of sCO2. In conclusion, further research should focus on two aspects. The first is to carry out more fundamental cascade experiments and numerical simulations to reveal the complex mechanisms for the near-critical, transonic, and two-phase flow within the sCO2 axial-flow compressor. The second is to develop loss models and design a space suitable for sCO2 multistage axial-flow compressors, thus improving the design tools for high-efficiency and wide-margin sCO2 axial-flow compressors.